Public Transportation in the West Bank Current Assessment and Future Prospects - Mahmoud Qasrawe; Motaz Abboshi; Raja Rabaya (My University, 2012)
The general objective of this research is to analyze and evaluate the current public transportation system and to explore areas of improvement for the industry. This study aims to find an optimal system of work of the public transport network, and mechanism of action between the companies concerned, and propose solutions that will improve the public transport system, and to provide better service for users.